(untitled) - Han, M. Y. (Singapore, 1999)
The major development in atomic, nuclear particle and quark physics are presented in this text. It provides a brief history of particles, charting the discovery of electrons and photons, antimatter, atomic nuclei, strong and weak forces, and quarks and gluons. In particular, it traces the concept of "conversed charges", a phenomena that is consistently manifested in each of the developments in modern physics.
Keywords: Particles (Nuclear physics),Hạt (vật lý hạt nhân); History,Lịch sử